2018
DOI: 10.1080/09647775.2018.1537608
|View full text |Cite
|
Sign up to set email alerts
|

Missing HRM: the original sin of museum reforms in Italy

Abstract: The Italian Ministry of Culture has been undertaking substantial reforms in the last decades, aimed at reorganizing both the museum sector and the local branches of the Ministry, the Superintendence system. By reconstructing the genealogy of these reforms from a management study perspective, the paper points out the overall misunderstanding of human resource issues in their design and implementation. Starting from the Pompeii reform in 1997 up to the Franceschini reform in 2014-2016, the authors focus on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Case selection was conducted through a documental analysis (Bowen 2009) performed on 30 PM websites by two researchers in order to exclude possible bias caused by the complexity of this activity. The selection of the sample has been conducted through the normative analysis of the Franceschini reform (2014-2016) that gave special autonomy to 30 Italian Museums (Zan et al 2018). On completion of the research, we identified 5 freely available IERs that represent 16% of our sample.…”
Section: Methodsmentioning
confidence: 99%
“…Case selection was conducted through a documental analysis (Bowen 2009) performed on 30 PM websites by two researchers in order to exclude possible bias caused by the complexity of this activity. The selection of the sample has been conducted through the normative analysis of the Franceschini reform (2014-2016) that gave special autonomy to 30 Italian Museums (Zan et al 2018). On completion of the research, we identified 5 freely available IERs that represent 16% of our sample.…”
Section: Methodsmentioning
confidence: 99%
“…The management of the other governmental museums still depends on the public sector administrations. In general, consider that governmental museums in Italy are still largely driven by a legislative-bureaucratic approach, though the recent reforms aimed to enhance the autonomy and the managerial perspective of museum directors (Zan et al, 2018). Clearly, the role played by museum services could be different according to the type of museum, the type of art collection and the consequent different degree of interactive fruition (let us think of fine arts museums versus science and technology museums).…”
Section: Institutional Feature Of Museums and The Case Of Italymentioning
confidence: 99%
“…In the analysis of reform is delineated the importance of the human resources (Zan et al, 2018) finalized to find a new approach for the management of human resources because around that there is the trouble on the low understanding of the notion of management.…”
Section: Museum's Reform and Economic And Financial Autonomymentioning
confidence: 99%
“…Another consideration, that permits to read these results, consists in the presence of human resource able to manage compliance to the requests and the know-how able to manage the areas of economic autonomy, bringing to the attention its "advantages" (Zan et a., 2018). Untrained human resources ready for the changes introduced, employees not aware of the advantage deriving from the use of accounting data implies a lack of understanding of the effects that autonomy can generate.…”
Section: Final Considerationsmentioning
confidence: 99%